Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content 1. The Effect of a training program based on Felder-Silverman model on improving reflective practices of Muslim bin Yasar Middle School teachers in Riyadh Mr. Ahmad Ali Al-Bariqi, Co-Prof. Ahmad Hasan Al-Bdour 2. STEM Program in Kindergarten in Australia and the possibility of benefiting from it in the Kingdom of Saudi Arabia Mrs. Tahani Mohammed Mougram Alshehri 3. Reality of employing Blockchain technology in educational process in Saudi universities from point of view of faculty members Mrs. Shorouk Abdullah Tael Al-Sawat 4. Employing artificial intelligence applications and their importance in the educational process from the point of view of computer teachers Dr. Ashwaq Dahman Qirqaji 5. Evaluation of the psychometric properties of the Arabic version of the Depression, Anxiety, and Stress Scale- 21 items (DASS-21) – A descriptive study on a sample of adolescents in Jeddah- Saudi Arabia Mrs. Walaa Salem Al-Shetaiwi, Co-Prof. Nawal Abdullah Al-Dhobaiban 6. The relationship of shyness to self-concept among upper elementary school students in the Area Al-Qasr Education Directorate Mrs. Rozeen Khalaf Mawadeh , Prof. Mikail Ibrahim